Functional disruption of α4 integrin mobilizes bone marrow–derived endothelial progenitors and augments ischemic neovascularization - Qin, Gangjian (The Rockefeller University Press, 2006)
The cell surface receptor α4 integrin plays a critical role in the homing, engraftment, and maintenance of hematopoietic progenitor cells (HPCs) in the bone marrow (BM). Down-regulation or functional blockade of α4 integrin or its ligand vascular cell adhesion molecule-1 mobilizes long-term HPCs. We investigated the role of α4 integrin in the mobilization and homing of BM endothelial progenitor cells (EPCs). EPCs with endothelial colony-forming activity in the BM are exclusively α4 integrin–expressing cells. In vivo, a single dose of anti–α4 integrin antibody resulted in increased circulating EPC counts for 3 d. In hindlimb ischemia and myocardial infarction, systemically administered anti–α4 integrin antibody increased recruitment and incorporation of BM EPCs in newly formed vasculature and improved functional blood flow recovery and tissue preservation. Interestingly, BM EPCs that had been preblocked with anti–α4 integrin ex vivo or collected from α4 integrin–deficient mice incorporated as well as control cells into the neovasculature in ischemic sites, suggesting that α4 integrin may be dispensable or play a redundant role in EPC homing to ischemic tissue. These data indicate that functional disruption of α4 integrin may represent a potential angiogenic therapy for ischemic disease by increasing the available circulating supply of EPCs.